In silico analysis of Mentha pipertia (phyto-constituents) as HMG coa reductase and squalene synthase inhibitors - Narayanaswamy, Radhakrishnan; Lam, Kok Wai; Ismail, Intan Safinar (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2018)
Mentha piperita has been well known for its hypolipidemic activity. This prompted the present study to be carried out on a selected 12 phyto-constituents of Mentha piperita which are naringin, eriodictyol, eriodictyol 7-glucuronide, eriocitrin, hesperidin, isorohifolin, luteolin 7-glucoside, diosmin, rosmarinic acid, piperitoside, menthoside and caffeic acid. These phyto-constituents were evaluated on the docking behaviour of HMG CoA reductase (HMGR) and Squalene synthase (SQS) using Discovery Studio Version 3.1. In addition, molecular physicochemical, drug-likeness, ADMET (Absorption, Distribution, Metabolism, Excretion and Toxicity) and TOPKAT (Toxicity Prediction by Komputer Assisted Technology) analyses were done. The molecular physicochemical analysis revealed that eriodictyol, rosmarinic acid and caffeic acid (3 ligands) complied with Lipinski’s rule of five. ADMET analysis showed that eriodictyol and caffeic acid exhibited good intestinal absorption property. Docking studies and binding free energy calculations revealed that menthoside (-70.0 kcal/mol) and piperitoside (-65.32 kcal/mol) exhibited the maximum interaction energy with HMGR and SQS respectively. Caffeic acid exhibited very least binding energy irrespective of its target protein. Caffeic acid showed interaction with Leu546 and Gln212 amino acid residue of HMGR and SQS. Hence, the results of this present study exhibited the potential of these twelve ligands as hypolipidemic agents.